Causation of the heavy rainfall in Kyushu in early July 2020: A perspective of the depression that originated over the Tibetan Plateau - Li, Lun; Huang, Honghui; Zhu, Congwen (Frontiers in Earth Science, 2023)
Heavy rainfall fell in Kyushu, Japan, in early July 2020, which caused huge life and economic losses. The present work reports that a Tibetan Plateau vortex (TPV) generated over the Tibetan Plateau is transformed to a trough at the eastern edge of the Tibetan Plateau, and the trough continues to move eastward and is responsible for the heavy rainfall in Kyushu. Accordingly, the maintenance and eastward movement of the trough, as well as the influencing mechanism of the trough on the rainfall in Kyushu are explored, based on the final analyses data (FNL) from NCEP and the JRA-55 reanalysis from JMA. Diagnoses of potential vorticity (PV) tendency equation indicate that the horizontal PV flux convergence east of the trough is the primary contributor to the eastward movement and maintenance of the trough. Furthermore, the trough is proved to have important effects on the moisture condition and the ascending motion around Kyushu. That is, the trough increases the moisture in Kyushu by intensifying the eastward moisture transportation to Kyushu; the positive vorticity and warm center, as well as the wind perturbation related to the trough are in favor of stronger ascending motion in Kyushu. The findings in this work give extended knowledge on the causation of rainfall falling in Japan, which is beneficial for the further precipitation prediction.